Association with cationized gelatin nanospheres enhances cell internalization of mitochondria efficiency - Wenxuan Yang; Satoshi Abe; Yasuhiko Tabata (Regenerative Therapy, 2023)
The objective of this study is to confirm the methodological feasibility of cationized gelatin nanospheres (cGNS) to enhance the internalization efficiency of mitochondria (Mt) isolated to cells for their increasing functions. The cGNS were simply associated on the surface of Mt by the electrostatic interaction. Different sizes of cGNS were used to allow Mt to associate on the Mt surface (Mt-cGNS). As a control, cationized gelatin (cG) was used to modify the Mt surface (Mt-cG). The Mt-cG and Mt-cGNS prepared were cultured with H9c2 cells to examine their internalization. The internalization efficiency significantly increased by utilizing cGNS. However, there was no significant difference in the internalization efficiency among cGNS with different sizes. After incubation of Mt, Mt-cG, and Mt-cGNS, the superoxide amount and ATP generation were evaluated. Significantly lower superoxide amount and higher ATP amount were observed for the Mt-cGNS group compared with those of non-modified Mt group. It is conceivable that cGNS enhance the cellular internalization of Mt, leading to an improve mitochondrial functions in the recipient cells. In conclusion, cGNS are promising to improve the efficacy in mitochondria internalization.